2015
DOI: 10.1063/1.4905672
|View full text |Cite
|
Sign up to set email alerts
|

Observation of 0–π transition in SIsFS Josephson junctions

Abstract: The 0–π transition in Superconductor-Insulator-superconductor-Ferromagnet-Superconductor (SIsFS) Josephson junctions (JJs) was investigated experimentally. As predicted by theory, an s-layer inserted into a ferromagnetic SIFS junction can enhance the critical current density up to the value of an SIS tunnel junction. We fabricated Nb′ | AlOx | Nb | Ni60Cu40 | Nb JJs with wedge-like s (Nb) and F (Ni60Cu40) layers and studied the Josephson effect as a function of the s- and F-layer thickness, ds and dF, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…This conclusion is also supported by experimental observations on SIsFS junctions [54][55][56]. These observations indicate that the introduction of a thin s interlayer, which should make a transition to the normal state if its thickness is of the order of the coherence length, shifts the 0-π transitions towards larger d .…”
Section: Comparison With Experimentssupporting
confidence: 71%
“…This conclusion is also supported by experimental observations on SIsFS junctions [54][55][56]. These observations indicate that the introduction of a thin s interlayer, which should make a transition to the normal state if its thickness is of the order of the coherence length, shifts the 0-π transitions towards larger d .…”
Section: Comparison With Experimentssupporting
confidence: 71%
“…The weakly ferromagnet NiCu was often used in fabrication of Nb based ferromagnetic Josephson junction. [21][22][23] The thickness of each layer was controlled by measuring the deposition rate and the deposition time. The deposition rate of the NbN and Ni 60 Cu 40 layers was 0.6 nm/s and 0.07 nm/s, respectively.…”
Section: Layer © 2018 Author(s) All Article Content Except Where Omentioning
confidence: 99%
“…Recent theoretical 5 and experimental 6 studies indicated a possible realization of the above mentioned transformations of I S (ϕ) in SIsFS structures in the form of instabilities near 0-π transition. So far, this new fundamental feature of the Josephson structures remains unexplored.…”
Section: Introductionmentioning
confidence: 97%